Flashboiling atomization in nozzles for GDI engines - Bornschlegel, Sebastian; Conrad, Chris; Eichhorn, Lisa; Wensing, Michael (28th Conference of Liquid Atomization and Spray Systems ILASS 2017, 6.-8.9.2017, Valencia. Spain, 2017)
Flashboiling denotes the phenomenon of rapid evaporation and atomization at nozzles, which occurs when fluidsare injected into ambient pressure below their own vapor pressure. It happens in gasoline direct injection (GDI) engines at low loads, when the cylinder pressure is low during injection due to the closed throttle valve. The fuel temperature at the same time approaches cylinder head coolant temperature due to the longer dwell time of the fuel inside the injector. Flash boiling is mainly beneficial for atomization quality, since it produces small droplet sizes and relative broad and homogenous droplet distributions within the spray. Coherently, the penetration depth normally decreases due to the increased aerodynamic drag. Therefore the thermal properties of injectors are often designed to reach flash boiling conditions as early as possible. At the same time, flash boiling significantly increases the risk of undesired spray collapsing. In this case, neighbouring jets converge and form a single jet. Due to the now concentrated mass, penetration depth is enhanced again and can lead to liner or piston wetting in addition to the overall diminished mixture formation.In order to understand the underlying physics, it is important to study the occurring phenomena flashboiling and jet-to-jet interacting i.e. spray collapsing separately. To this end, single hole injectors are built up to allow for an isolated investigation of flashboiling. The rapid expansion at the nozzle outlet is visualized with a microscopic high speed setup and the forces that lead to the characteristic spray expansion are discussed. Moreover, the results on the macroscopic spray in terms of penetration, cone angles and vapor phase are shown with a high speed Schlieren setup. Resulting droplet diameters and velocities are measured using LDA/PDA.As a result, we find a comprehensive picture of flash boiling. The underlying physics can be described and discussed for the specific case of high pressure injection at engine relevant nozzle geometries and conditions, but independently from neighbouring jets. These findings provide the basis to understand and investigate flashboilingand jet-to-jet interaction as distinct, but interacting subjects rather than a combined phenomeno